Medicine shortages: impact behind numbers - Doerine J. Postma; Kim Notenboom; Peter A. G. M. De Smet; Hubert G. M. Leufkens; Aukje K. Mantel-Teeuwisse (Taylor & Francis Group, 2023)
Abstract Introduction Current research to assess the impact that medicine shortages have on patients is limited to general aspects, such as the prevalence of shortages and product characteristics. The aim of this study is to assess the overall impact that medicine shortages have on economic, clinical, and humanistic outcomes. Methods A cohort of all known products in shortage in the Netherlands between 2012 and 2015 were characterized by their route of administration, anatomical therapeutic chemical class, and whether they were originator or generic products. A representative sample of 324 shortages (18% of all shortages) was rated as having low, medium, or high impact on the five elements that determine the impact of shortages on patients: availability of an alternative product, underlying disease, susceptibility of the patient, costs (for patients and society at large), and number of patients affected. Ratings were converted into numerical scores per element and multiplied to obtain an overall impact score. Results Two elements were most frequently rated as having a high impact: disease (29%) and costs (20%). Nearly half of the shortages (47%) rated high on at least one element, while nearly 10% rated high on multiple elements. Thirty percent of the shortages rated high on direct impact, which is represented by these elements: alternative product and disease. An additional 17% of the shortages rated high on indirect impact, which is represented by these elements: costs, susceptibility, and number of patients. High impact scores could not significantly be attributed to characteristics of the products in shortage. Conclusions An assessment of the medicine shortages' impact using a framework based on economic, clinical, and economic outcomes showed that all three outcomes affect the overall impact that medicine shortages have on patients.